2011
DOI: 10.1007/s00300-011-1139-2
|View full text |Cite
|
Sign up to set email alerts
|

Widespread amplification of amplified fragment length polymorphisms (AFLPs) in marine Antarctic animals

Abstract: Although recent years have witnessed a rapid growth in the number of genetic studies of Antarctic organisms, relatively few studies have so far used nuclear markers, possibly due to the perceived cost and diYculty of isolating markers such as microsatellites. However, an often overlooked alternative is to use ampliWed fragment length polymorphisms (AFLPs), a versatile and low-cost method capable of generating large numbers of predominantly nuclear loci in virtually any organism. We conducted a literature revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 70 publications
0
8
0
Order By: Relevance
“…This study was made feasible through the use of AFLPs because these markers are capable of generating large numbers of genome-wide distributed bands in virtually any organism, including diverse Antarctic marine taxa [61], with little need for optimisation. Although we were able to score a large number of bands, however, the dominant nature of these markers leads to increased variance in the estimation of allele frequencies [54].…”
Section: Discussionmentioning
confidence: 99%
“…This study was made feasible through the use of AFLPs because these markers are capable of generating large numbers of genome-wide distributed bands in virtually any organism, including diverse Antarctic marine taxa [61], with little need for optimisation. Although we were able to score a large number of bands, however, the dominant nature of these markers leads to increased variance in the estimation of allele frequencies [54].…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, a study using COI demonstrated no apparent genetic structure along the South Shetland Islands and Antarctic Peninsula, supporting a single genetic unit along this area, which could be the result of past bottleneck events during the glacial maxima and further founder effects (González-Wevar et al, 2011). On the other hand, another study using AFLP markers found significant differences between one of the Southern-most areas surveyed (Anchorage Island, South to Adelaide Island) and the rest of the localities (Hoffman et al, 2012). The results for N. concinna contrast with those obtained for the bivalve Margarella antarctica.…”
Section: Molluscsmentioning
confidence: 93%
“…A range of markers including ribosomal genes (18S and 28S rDNA) and internal transcribed spacers (ITS1 and ITS2), Exon-primed Intron-crossing (EPIC) markers, and microsatellites have also been applied in some Antarctic species (see Table 1). In addition, Amplified Fragment Length Polymorphism (AFLP) techniques have also been used in two studies on Antarctic organisms (Hoffman et al, 2011(Hoffman et al, , 2012; see Table 1). However, the reduced number of examples studied hinders the comprehensive comparisons among taxa.…”
Section: Molecular Markers For Genetic Diversity and Connectivitymentioning
confidence: 99%
“…The aim of this study was to explore the genetic diversity and population structure of two declining chinstrap penguin populations from the South Shetland Islands using amplified fragment length polymorphism (AFLP) analyses (Busch et al 2000;Milot et al 2008;Hoffman et al 2012). Falling population sizes can lead to loss of neutral genetic variation, fixation of mildly deleterious alleles, and thereby reduced population fitness (Kalinowski and Waples 2002;Baker 2006;Markert et al 2010).…”
Section: Introductionmentioning
confidence: 99%